PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN JOB RELEVANT INFORMATION, KEPUASAN KERJA DAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Nengsy, Herda; Sari, Ria Nelly; Agusti, Restu (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
Performance is an important part of an organization, either a business or nonbusiness. To perform well, it is very dependent on the role of a manager. Thus, oneof success measurements of an organization is its managerial performance. Thepresent research seeks to investigate the effect of budget preparation participationon the managerial performance with job relevant information, job satisfaction andmotivation as the intervening variables. The inconsistencies of the previous researchof the effect of the budget preparation participation on the managerial performancebecome the motivation of the present research.The present research is a survey inwhich data were collected using a questionnaire distributed to the SKPD StructuralOfficials of consisting of Echelon II, Echelon III and Echelon IV at the RegionalGovernment of Indragiri Hilir Regency. Of the 213 distributed questionnaires, 159 ofthem were returned. Based on the criteria standard, there were 132 questionnairesto be calculated in the present research. The analysis method was Variant-basedSEM using SmartPLS Version 2.0. The results show that the budget preparationparticipation has no direct correlation with the managerial performance. It has arelationship with the managerial performance through job satisfaction andmotivation. The research could not prove that job relevant information is anintervening variable between the budget preparation participation and managerialperformance.Keywords: budget preparation participation, job relevant information, jobsatisfaction, motivation, managerial performance, partial least square